Divergent outcomes following transcytosis of IgG targeting intracellular and extracellular chlamydial antigens - Armitage, Charles W (2014)
Antibodies can have a protective but non-essential role in natural chlamydial infections dependent on antigen specificity and antibody isotype. IgG is the dominant antibody in both male and female reproductive tract mucosal secretions, and is bi-directionally trafficked across epithelia by the neonatal Fc receptor (FcRn). Using pH-polarized epididymal epithelia grown on Transwells, IgG specifically targeted at an extracellular chlamydial antigen; the major outer membrane protein (MOMP), enhanced uptake and translocation of infection at pH 6–6.5 but not at neutral pH. This was dependent on FcRn expression. Conversely, FcRn-mediated transport of IgG targeting the intracellular chlamydial inclusion membrane protein A (IncA), induced aberrant inclusion morphology, recruited autophagic proteins independent of lysosomes and significantly reduced infection. Challenge of female mice with MOMP-specific IgG-opsonized Chlamydia muridarum delayed infection clearance but exacerbated oviduct occlusion. In male mice, MOMP-IgG elicited by immunization afforded no protection against testicular chlamydial infection, whereas the transcytosis of IncA-IgG significantly reduced testicular chlamydial burden. Together these data show that the protective and pathological effects of IgG are dependent on FcRn-mediated transport as well as the specificity of IgG for intracellular or extracellular antigens.